HUBUNGAN INDEKS MASSA TUBUH, JENIS KELAMIN, USIA, GOLONGAN DARAH DAN RIWAYAT KETURUNAN DENGAN TEKANAN DARAH PADA PEGAWAI NEGERI DI PEKAN BARU - Heryudarini Harahap; Hardinsyah Hardinsyah; Budi Setiawan; Imam Effendi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2008)
AbstractBackground: The increasing prevalence of hypertension is an important public health problem contributing to significant excess disease and mortality. The risk factors of high blood pressure were obesity, sex difference, aged, and heredity. Some factors had clearly evidence that had relationship with blood pressure, but other had not clearly, e.g. blood group. Objectives: To study the relationship between BMI, sex, age, blood group and heredity of hypertension with blood pressure. Methods: A cross-sectional survey was conducted in Pekan Baru. Subjects were government employee. Blood pressure was collected using sphygmanometer. Weight were collected.by SECA and height by microtoice. Blood group, sex, age, heredity was collected using questionaire. The JNC 7 was used to classify of hypertension. Results: A subject of 510 government employee aged 30 – 55 years was selected in Pekan Baru. The prevalence of pre-hypertension was 37,6% and hypertension was 10,4%. The prevalence of overweight and obese (BMI ≥ 25,0) was 60,6%. BMI was positively associated with systole blood pressure (SBP). This study found that every BMI unit increase was associated with an SBP increase of 0,362 mmHg for men and women. Diastole blood pressure (DBP) of women was lower 3,4 point than men. There was positively associated between aged and systole/diastole. Every one year increase was associated with an SBP increase of 0,493 mmHg, and 0,189 mmHg DBP. Blood group was not associated with SBP, and DBP but SBP of AB blood groups was lower than A, B or O blood group; and DBP was lower than B blood group. There was strong association between heredity hypertension and SBP, and DBP. SBP of subject that had hypertension heredity was higher 4,8 mmHg, and diastole was higher 3,5 mmHg than subject without heredity hypertension. Conclusions: There was positively associated between BMI and SBP; between aged and SBP, and DBP. Men had higher DBP than women. Subject that had hypertension heredity had higher SBP, and DBP than subject without hypertension heredity. [Penel Gizi Makan 2008, 31(2): 51-58]   Keywords: blood pressure, BMI, sex, age, heredity, blood group